Perspective of sarcoidosis in terms of rheumatology: a single-center rheumatology clinic experience - ÖZ, NURAN; DURUÖZ, MEHMET TUNCAY (My University, 2022)
Sarcoidosis may present with many rheumatological symptoms as well as mimic and/or may occur concomitantly with many other rheumatic diseases. We examined the demographic, clinical and laboratory characteristics of patients diagnosed with sarcoidosis in the rheumatology department. This study planned as retrospective cross-sectional study. Medical records of patients who applied to our rheumatology outpatient clinic due to complain of musculoskeletal problems and then diagnosed sarcoidosis were retrospectively investigated. Joint findings, extrapulmonary involvements, and coexisting rheumatic disease were evaluated. Fifty-six patients (41.21 +/- 7.83 years, 75% female) were included. The duration of the disease was 49.61 +/- 29.11 months, and the follow-up period was 26.66 +/- 13.26 months. All patients had pulmonary system involvement. Arthralgia was present in 91.10% of 56 patients and arthritis in 89.29% of patients. Examining the subtypes of the arthritis findings, mono-arthritis was found in 31/50 (62%) patients, oligo-arthritis in 15/50 (30%) patients, and polyarthritis in 4/50 (8%) patients. A total of 11 (19.60%) patients were diagnosed with uveitis. Excision of the mediastinal LAP was performed in a total of 37 patients (66.1%) and became the most commonly employed method. Considering the treatment distribution of the patients under followed-up, it is seen that non-steroidal anti-inflammatory treatments were used in 15 (26.8%) patients, corticosteroids in a total of 40 (71.4%) patients, methotrexate in a total of 15 patients (26.8%), azathioprine in six (10.7%) patients, hydroxychloroquine in 14 (25%) patients, and infliximab in one (1.8%) patient. As sarcoidosis is a mimicking disease, a good differential diagnosis should be made to avoid misdiagnosis and in order not to be late in diagnosis and treatment. Physicians, especially rheumatologists, should remember sarcoidosis more frequently as the disease may overlap with other rheumatological diseases and may occur with many rheumatological manifestations.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Health Sciences; ROMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); RHEUMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Romatoloji; Rheumatology; Sarcoidosis; Organ ınvolvement; Arthritis